2024
DOI: 10.3390/buildings14010146
|View full text |Cite
|
Sign up to set email alerts
|

Study on Numerical Simulation of Arch Mechanism of Bridge Pile Foundation

Zhanhui Qu,
Zemin Han,
Haoyu Tang
et al.

Abstract: Bridges are situated in a complex area with geological conditions that are challenging for engineering. It has been observed that certain pile foundations of bridges have been uplifted to varying degrees by up to 309 mm. This has a significant impact on the bridge’s operation and driving safety. The causal mechanism of the bridge pile foundation arch is analyzed through a theoretical analysis and a Plaxis 3D (v.2013) finite element software simulation. The influence of the ground stress and goaf on the bridge … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
(11 reference statements)
0
0
0
Order By: Relevance
“…In addition, the large-scale lifting of groundwater reduces the effective stress of the overlying soil under the pile foundation, and the buoyancy generated by groundwater causes the overlying soil to lose its load as a whole, eventually leading to the overall upward floating of the pier [21]. Qu et al [22] analyzed the influencing factors of bridge pile foundation arch by using Plaxis 3D finite element software simulation, and concluded that ground stress is the main reason for bridge pile foundation arch. Zheng et al [23] proposed a novel complex true triaxial static-dynamic combined loading method reflecting underground excavation damage and frequent intermittent disturbance failure and also proposed a new three-stage true triaxial coupled static and dynamic load test method to simulate the stress path of rock in the process of disturbance and failure after deep engineering excavation.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the large-scale lifting of groundwater reduces the effective stress of the overlying soil under the pile foundation, and the buoyancy generated by groundwater causes the overlying soil to lose its load as a whole, eventually leading to the overall upward floating of the pier [21]. Qu et al [22] analyzed the influencing factors of bridge pile foundation arch by using Plaxis 3D finite element software simulation, and concluded that ground stress is the main reason for bridge pile foundation arch. Zheng et al [23] proposed a novel complex true triaxial static-dynamic combined loading method reflecting underground excavation damage and frequent intermittent disturbance failure and also proposed a new three-stage true triaxial coupled static and dynamic load test method to simulate the stress path of rock in the process of disturbance and failure after deep engineering excavation.…”
Section: Introductionmentioning
confidence: 99%